Supporting South Asian Taxi Drivers to Exercise through Pedometers (SSTEP) to Decrease Cardiovascular Disease Risk - Gany, Francesca (Springer US, 2014)
There is considerable evidence demonstrating the positive impact of pedometers and walking programs for increasing physical activity and reducing risk for cardiovascular disease among diverse populations. However, no interventions have been targeted towards South Asian taxi drivers, a population that may be at high risk for developing cardiovascular disease. Supporting South Asian Taxi Drivers to Exercise through Pedometers (SSTEP) was a 12-week pilot study among South Asian taxi drivers to increase their daily step counts. SSTEP assessed the feasibility, acceptability, and potential impact of an exercise intervention employing pedometers, a step diary, written materials, and telephone follow-up to initiate or increase physical activity in this at-risk occupational group. Seventy-four drivers were recruited to participate at sites frequented by South Asian taxi drivers. Participant inclusion criteria were: (1) age 18 or over; (2) birthplace in India, Pakistan, or Bangladesh; (3) fluent in English, Hindi, Urdu, Punjabi, or Bengali; and (4) intention to remain in New York City for the 3-month study period. Comprehensive intake and exit questionnaires were administered to participants in their preferred languages. Intake and exit health screenings, including blood pressure, cholesterol, and glucose were completed. Daily step counts were obtained 4 days after recruitment, and at the 4-, 8-, and 12-week mark via phone calls. To measure the impact of the intervention, step counts, blood pressure, cholesterol, and body mass index were compared at intake and exit. Participants in SSTEP were sedentary at baseline. The SSTEP intervention resulted in a small increase in step counts among participants overall, and in a significant increase (>2,000 steps) among a subset (“Bigsteppers”). Drivers with higher baseline glucose values had significantly greater improvements in their step counts. Focused lifestyle interventions for drivers at high risk for cardiovascular disease may be particularly impactful.